Short Communication Biochemical and Molecular Genetic Studies on Some Cyanobacterial Isolates: Short Communication: Cynobacterial Isolation - Kamel, Ehab Abdel-Razik; Ebrahim, Samier Abdel-Aziz; Tawab Thabet, Rabea Abdel-; Rabea El-Shal, Engy Mohamed (Biological Sciences - PJSIR, 2011)
In the present study, the isolation and purification of a set of Cyanobacteria strains belonging to genus Oscillatoria was undertaken, followed by the analyses of phylogenetic relationships using different biochemical and molecular genetic techniques (SDS-PAGE and RAPD-PCR). A total of 45 protein bands were observed within the studied Oscillatoria isolates by SDS-PAGE (only three unique bands, eight monomorphic bands and 37 polymorphic bands). On the other hand, extracted DNA from isolates was used to identify the molecular fingerprints. A sum of 94 polymorphic bands was generated by these primers in the Ocsillatoria genotypes under study. A total of 20 unique bands were identified out of the polymorphic ones. These unique bands were used to discriminate among the studied Ocsillatoria isolates. Most isolates of Ocsillatoria genotypes were discriminated by one or more unique bands. Numerical taxonomic using 45 protein attributes of 19 isolates and RAPD markers on five isolates. Two methods - Clustering (UPGMA) and Principal Component Analysis (PCA) were used for these analyses. The similarities and clusters produced between the studied isolates were discussed.